#### Answer

$y' = x^{2}e^{x}(x+3)$

#### Work Step by Step

$y = x^{3}e^{x}$
$y' = x^{3}e^{x} + 3x^{2}e^{x}$
$y' = x^{2}e^{x}(x+3)$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y' = x^{2}e^{x}(x+3)$

$y = x^{3}e^{x}$
$y' = x^{3}e^{x} + 3x^{2}e^{x}$
$y' = x^{2}e^{x}(x+3)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.